Comparison of Electronic Medical Records between A Personalcomputer and Android Tablet in A Hospital - Raihan, Siti Luluk; Haris, Amin; Maidar, Maidar; Abdullah, Asnawi; Aramico, Basri (Indonesian Journal of Global Health Research, 2024)
The transformation of the health sector consists of six pillars, one of which is the transformation of health technology. The electronic medical record is the collection, storage, processing, and access of patient medical record data in hospitals using information technology. The Minister of Health, in Regulation of the Minister of Health number 24 of 2022, requires all health service facilities to maintain electronic medical records. In this study, research was conducted on the process of collecting, storing, processing, and accessing medical data at the ERM in a hospital using a personal computer and an Android tablet. This research uses a qualitative case study method that investigates phenomena in real-life contexts and is examined in a case that is carried out intensively, in depth, in detail, and comprehensively. The independent variable is the process of collecting, storing, processing, and accessing medical record data, and the dependent variable is electronic medical records. Data was collected by observing the patient's medical record recording process and interviewing informants consisting of registrars, doctors, nurses, laboratory staff, hospital IT personnel, and hospital administration; triangulation was then carried out on the data obtained. The results of the study found that the process of collecting medical record data on personal computer media was different from that on Android tablet media, from the method of writing to the results of recording medical records. However, the flow from recording to storage, access, processing, and security of medical record data is not much different In the implementation of electronic medical records, there are advantages and disadvantages to each medium, but it would be better if a combination of the two was carried out. In order to create continuity in the process of recording medical records in electronic media.